Impacto da recuperação dos investimentos na infraestrutura hídrica (barragens e adutoras) sobre a cobrança pelo uso da água - Aquino, Tiago Silveira de Andrade (2010)
The water infrastructure projects generally esbaram the problem of lack of financial resources for the construction and operation. It then becomes the hypothesis of obtaining the funds for construction of water infrastructure by charging for the use of raw water. The question is then what is the impact on water charges if the cost of building the water infrastructure was applied to the charging for the use of raw water, together with the costs of AOM (Administration, Operation and Maintenance). We evaluated the financial cost of deployment of storage systems and water transfer activities in water supply, comparing the unit cost of raw water with the ability to pay of water users. data was used for construction of reservoirs and aqueducts in Ceara, we calculated the annuity payment for these works by applying current variables of time and interest payment. With the annual flow regulated and the cost of construction of the works, one could estimate a cost for this water, and thus compare it to the current user fees and their ability to pay. Could observe a relationship between construction costs of infrastructure and flow regulated supply of equipment studied (dams and pipelines). The best trend line that fit the scatter plots between the estimated cost of supply for the payment of infrastructure "versus" flow was regulated power curve. The values ​​obtained for the ability to pay in other published works (Marques, 2009 and Tahal, 2003) were within an order of magnitude of the values ​​obtained in this work, leading to consider that there is the possibility of payment of these works, so amortized, for users not making totally impractical